Egypt - Karlsson, Val. (Edina, Minn. : ABDO Pub. Co., 2012)
An examination of modern Egypt, an ancient land now struggling to modernize and democratize its society.
A visit to Egypt -- Geography : land of the Nile -- Animals and nature : ancient symbols -- History : where civilization began -- People : modern Egyptians -- Culture : collision of old and new -- Politics : a country in transition -- Economics : limited opportunities -- Egypt today.
Includes bibliographical references (p. 136-137) and index.
Keywords: Egypt -- Juvenile literature; Egypt